National Uranium Resource Evaluation Aerial Gamma Ray and Magnetic Reconnaissance Survey, Southeastern Area, Alaska - LKB Resources, Inc. (United States. Department of Energy. Grand Junction Office., 1979)
Second volume of a report documenting a high-sensitivity airborne radiometric and magnetic survey of the Dixon Entrance quadrangle including maps documenting geophysical and geochemical data, as well as magnetic, ancillary and radiometric data.